2019
DOI: 10.1186/s12906-019-2593-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of, and factors associated with health supplement use in Dubai, United Arab Emirates: a population-based cross-sectional study

Abstract: Background Health supplement (HS) products that are available in the Emirate of Dubai (United Arab Emirates; UAE) contain chemicals that may adversely affect human health. This study aimed to investigate the prevalence of, and factors associated with HS consumption, knowledge, related adverse events, and reporting practices of adverse events amongst the general population in Dubai, UAE. Methods A cross-sectional household telephone survey using a computer-assisted quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 33 publications
5
22
0
Order By: Relevance
“…Our study showed that women used NSs, such as calcium and multivitamins, more often than men. This result is consistent with previous studies that have shown a higher interest in NS use among female consumers ( 25 27 ). Some researchers attribute this to women being more concerned than men about their health, as they feel more responsible for the wellbeing of other family members ( 2 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed that women used NSs, such as calcium and multivitamins, more often than men. This result is consistent with previous studies that have shown a higher interest in NS use among female consumers ( 25 27 ). Some researchers attribute this to women being more concerned than men about their health, as they feel more responsible for the wellbeing of other family members ( 2 ).…”
Section: Discussionsupporting
confidence: 93%
“…The higher consumption of these compounds was also noted in two cross-sectional studies in Poland, and improving immunity was found to be the main reason for supplementation ( Hamulka et al, 2021 ). Even though DDS may be generally regarded as safe, some of these substances may have a wide range of possible actions, and their uncontrolled use may lead to potentially hazardous interactions with commonly used medications, particularly among the elderly ( Abdulla et al, 2019a ). For example, garlic and ginger can increase the risk of bleeding when administered with anticoagulants ( Moyad, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of alternative remedies like DDS for the management of diseases in the United Arab Emirates (UAE) as in the Middle East is a widespread practice that has historical, traditional, and religious roots ( Ahmed et al, 2015 ; al Marshedi et al, 2017; AlBraik et al, 2008 , Dha, 2011 , Ibrahim et al, 2019 , Muttappallymyalil et al, 2013 , Sridhar et al, 2017 ). Before the COVID-19 pandemic, studies have estimated the prevalence of DDS use to be between 35% and 39% in the UAE ( Abdulla et al, 2019b , Alhomoud et al, 2016 , Radwan et al, 2019 ). The UAE is an ethnically diverse country where the practice and consumption of DDS may vary widely among its population groups.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, over-the-counter (OTC) or non-prescribed medications and health supplements are widely available for citizens worldwide including in the Emirate of Dubai (United Arab Emirates; UAE). 1 Consumers usually use OTC drugs and supplements without having prior knowledge about the dosage, drug-drug interactions, and contraindications. While this inappropriate use of OTC drugs and dietary supplements can increase the chances of potential side effects and may harm human health.…”
Section: Introductionmentioning
confidence: 99%